Transparancy Urgency of Non-Govermental Organization as a Public Body to Provide Information Accessible To Public - Edi Pranoto (Universitas Muhammadiyah Palu, 2024)
Lembaga Swadaya Masyarakat (LSM) is a local term that appeared in Indonesia to replace the term Ornop as a translation of Non-Governmental Organization (NGO). NGO together with the government and the private sector have a role to play in realizing good governance. Because of the strategic role of the NGO, it also requires good governance for NGO so that in the process of manifesting their roles can be accounted for to the community.The approach used to solve problems in scientific articles in the form of conceptual thinking uses normative approach methods, with skunder data sources, which are primary, skunder and tertiary legal materials. Law No. 14 of 2008 on Public Information Disclosure, classifies that non-governmental organizations whose sources of financing come from all or as from the State Budget/APBD, community donations, and/or foreign aid are public bodies. As a public body, NGO have an obligation to provide public information that is periodic, immediately and at any time that is easily accessible to the public. The urgency of transparency in the management of NGO can be seen from philosophical, juridical and sociological aspects. With the transparency of NGO management, there will be no more suspicions about NGO in Indonesia.